Surviving schizophrenia : a manual for families, consumers, and providers - Torrey, E. Fuller (Edwin Fuller), 1937- (New York : HarperPaperbacks, 2006)
Since its first publication in 1983, Surviving Schizophrenia has helped thousands of patients, families, and mental health professionals understand this complex and often stigmatized illness. In clear, sympathetic language, this definitive book describes the nature, causes, symptoms, and history of schizophrenia, taking readers inside the minds of those living with the disease. This new, completely updated fifth edition includes the latest research findings on all aspects of the disease as well as information about the newest treatments and answers to the questions most often asked by families, patients, and providers. Book jacket.
Includes bibliographical references and index.
Keywords: Schizophrenia -- Popular works; Schizophrenia -- Popular Works; Schizophrenia